Acquisition of English prepositions among Malaysian learners: a case study - Sudhakaran, Beena (Canadian Center of Science and Education, 2015)
Educationists are often in a predicament as to whether grammar should be taught formally, or whether it can be deliberately learned. This question is especially pertinent in Malaysia where there has been a general deterioration of grammar skills among English as a second language (ESL) learner. A prospective case study was carried out on seven Malay students from the International Islamic University Malaysia. The study sought to determine the extent to which students acquired English prepositions in the naturalistic setting in the written mode, the different types of errors, the use of alternative locative frames, and whether there was a specific pattern in the learning of prepositions. The study used writing tasks where students were required to write essays as well as make journal entries. Data was collected at six monthly intervals over three years. An analysis of students’ use of prepositions was carried out to monitor progress. It was found that most subjects had improvements in their use of prepositions, with more errors of commission than omission. One of the most common errors was the unnecessary use of the phrase involving a preposition, ‘for me’. Persistent errors could arise due to incomplete linguistic rule formation and transfer from the students’ first language (L1). There were also instances of other words like adverbs being used instead of prepositions. The best improvement was seen in the prepositions ‘for’, ‘in’ and ‘about’. These findings necessitate the need for corrective feedback on errors, and for grammar instruction to be compatible with the natural processes of acquisition.